Ospitalità mediatica Le migrazioni nel discorso pubblico - Musarò, Pierluigi (FrancoAngeli, 2022)
In a world divided by inequalities and on the verge of human extinction caused by climate change, we invoke security against the threat of immigration, perceived as a threatening disorder. In implementing all the devices designed to protect "us" and exclude "them", we believe in the illusion that it is sufficient to consolidate our fortresses to cope with the pressure of migratory flows. Yet we forget that there can be no humanity without hospitality. Exploring the tension between globalization processes and the spectacularisation of borders, the book invites us to rethink hospitality in the mediapolis as a cultural and political issue, offering concrete tools to amplify the voices of the protagonists of migration and create architectures so that their voices can be heard. Because we are all migrants, have been or may become migrants.